2003
DOI: 10.1177/0011000003031003008
|View full text |Cite
|
Sign up to set email alerts
|

Asian Cultural Values, Attitudes toward Seeking Professional Psychological Help, and Willingness to See a Counselor

Abstract: The purpose of this study was to examine the relationships among Asian American adherence to Asian cultural values, attitudes toward seeking professional psychological help, and willingness to see a counselor. Based on the data from 242 Asian American college students, the results revealed that adherence to Asian cultural values inversely predicted both attitudes toward seeking professional psychological help and general willingness to see a counselor, above and beyond the effects of related demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
254
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(282 citation statements)
references
References 22 publications
24
254
2
1
Order By: Relevance
“…Consistent with this idea, Kim and Omizo (2003) found that Asian Americans with high adherence to Asian values had less positive attitudes toward psychological help seeking and less willingness to see a counselor in general or for personal and health-related problems. With regard to the counseling process, several studies have found that high adherence to Asian cultural values were related to positive evaluations of counselors (Kim, Ng, & Ann, 2005).…”
mentioning
confidence: 73%
“…Consistent with this idea, Kim and Omizo (2003) found that Asian Americans with high adherence to Asian values had less positive attitudes toward psychological help seeking and less willingness to see a counselor in general or for personal and health-related problems. With regard to the counseling process, several studies have found that high adherence to Asian cultural values were related to positive evaluations of counselors (Kim, Ng, & Ann, 2005).…”
mentioning
confidence: 73%
“…These studies were Chung, Kim, and Abreu (2004); Kim and Atkinson (2002); Kim et al (1999); ; Kim, Hill, et al (2003); Kim, Li, and Ng (2003); Kim and Omizo (2003);and Liang, Li, and Kim (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Kim and Omizo (2003) In sum, these studies suggest that acculturation has an important implication on Asian American's attitudes toward seeking psychological services. Yet, it should be note that the samples of these studies were all college students.…”
Section: Attitudes Toward Seeking Psychological Servicesmentioning
confidence: 84%